2008
DOI: 10.1161/atvbaha.108.168682
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin Synthase 2 Deficiency Attenuates NFκB Activation

Abstract: Background-NFB has long been regarded as a proatherogenic factor, mainly because of its regulation of many of the proinflammatory genes linked to atherosclerosis. Metabolism of sphingomyelin (SM) has been suggested to affect NFB activation, but the mechanism is largely unknown. SMS2 regulates SM levels in cell plasma membrane and lipid rafts and has a potential to regulate NFB activation. Methods and Results-To investigate the role of SMS2 in NFB activation we used macrophages from SMS2 knockout (KO) mice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
130
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(138 citation statements)
references
References 34 publications
(41 reference statements)
8
130
0
Order By: Relevance
“…Confirmation of the involvement of SMS2 in the physiological maintenance of plasma membrane SM has come from studies using macrophages from SMS2 knock out (KO) mice. 76 Macrophages from SMS2 KO mice showed diminished recruitment of the Toll Like Receptor 4-MD2 complex on the cell surface in response to lypopolysaccharide (LPS) treatment, consistent with the reduction of LPS-mediated apoptosis observed in THP-1-derived macrophages after siRNA-mediated down-regulation of SMS1 or SMS2. 77 Likewise, siRNA-mediated down-regulation of SMS2 in HEK 293 cells partly inhibited recruitment of the tumor necrosis factor (TNF) _ receptor 1 to detergent-resistant microdomains in response to stimulation with TNF, decreasing TNF-mediated down-stream signaling.…”
Section: Sms1 and Sms2 As Regulators Of Sm Homeostasis And Receptor-msupporting
confidence: 58%
See 2 more Smart Citations
“…Confirmation of the involvement of SMS2 in the physiological maintenance of plasma membrane SM has come from studies using macrophages from SMS2 knock out (KO) mice. 76 Macrophages from SMS2 KO mice showed diminished recruitment of the Toll Like Receptor 4-MD2 complex on the cell surface in response to lypopolysaccharide (LPS) treatment, consistent with the reduction of LPS-mediated apoptosis observed in THP-1-derived macrophages after siRNA-mediated down-regulation of SMS1 or SMS2. 77 Likewise, siRNA-mediated down-regulation of SMS2 in HEK 293 cells partly inhibited recruitment of the tumor necrosis factor (TNF) _ receptor 1 to detergent-resistant microdomains in response to stimulation with TNF, decreasing TNF-mediated down-stream signaling.…”
Section: Sms1 and Sms2 As Regulators Of Sm Homeostasis And Receptor-msupporting
confidence: 58%
“…Moreover, SMS1 and a pool of SMS2 are both localized to the Golgi. 58,66,72,74,76 Why is this organelle equipped with two different SMS enzymes? What is the relevance of the reverse activity of SMS enzymes?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that SMS2 deficiency attenuates NF-kB signaling, thereby suggesting a role for ceramide in NF-kB signal transduction (63). However, ceramide also inhibits NF-kB activation (64)…”
Section: Sm Synthase 2 and Alimentioning
confidence: 99%
“…29 Protection from LPS-induced cell death has been further shown to be mediated by an impaired membrane recruitment of TLR4 signaling complexes in macrophages of SMS2 knockout mice. 30 This study aimed at investigating the function of SM biosynthesis in the regulation of FasL-induced cell death. We show that Fas-mediated apoptosis is associated with a profound inhibition of SM synthesis, which likely involved the caspase-mediated cleavage and relocation of SMS1.…”
mentioning
confidence: 99%